2004
DOI: 10.1108/09556220410520333
|View full text |Cite
|
Sign up to set email alerts
|

On‐demand production system of apparel on the basis of Kansei engineering

Abstract: This paper argues for the immediate use of Kansei engineering to help deal with the chaotic situation of poorly implemented and disconnected technologies. A theoretical criticism of the current industrial capitalism, together with the promotion of a new post-industrial form of capitalism, lays the foundation for an explanation of how this transition can be achieved through a proper understanding of Kansei. A detailed explanation of the interactive production system apparel demonstrates the benefits to both man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 0 publications
0
16
0
3
Order By: Relevance
“…Compared with their first launch, the sales of many products tend to decrease over time. This situation forces companies to reconsider their product design and development strategies (Shimizu et al 2004). Companies must listen closely and carefully to the voices of their customers, especially their latent needs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with their first launch, the sales of many products tend to decrease over time. This situation forces companies to reconsider their product design and development strategies (Shimizu et al 2004). Companies must listen closely and carefully to the voices of their customers, especially their latent needs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the distinction between emotions elements can be subtle and can be changed for example by one's cultural influence or personality traits. In the literature, the notion of emotional responses or known as affective elements have received significant attention and interest from the researchers [9][10][11] varies in its domain and dimensions in cooperating the values into the design conception, such as website design [11][12], clothing [13][14] and consumer products [15]. However in design practice, emotions are elicited by product appearance and often considered to be intangible, non-functional, non-rational or non-cognitive [8].…”
Section: Emotional Designmentioning
confidence: 99%
“…Previous studies (Shimizu et al, 2004;Ying & Yan, 2006) found that putting feelings, emotion, or psyche into an object/artifact, may increase values of object.…”
Section: The Acquisition Of Kansei Attributes and Its Measurement Appmentioning
confidence: 99%